Investigation of the favorable conditions to apply the combination resonances approach for crack detection purposes. (8th January 2020) - Cavalini, Aldemir A; Morais, Tobias S; da Silva, Izabela B; Bachschmid, Nicolò; Steffen, Valder
Various structural health monitoring methods were recently applied to fault diagnosis of rotating machinery, in which vibration response–based techniques demonstrated to be well adapted for different scenarios. However, only severe cracks are detected when most of such techniques are applied. Thus, innovative methods are proposed to identify the existence of incipient cracks in rotating shafts. In a previous contribution, the combination resonance approach for crack identification purposes was presented. This method is based on the application of additional forces at combination frequencies along with a heuristic optimization method to identify crack signatures in the vibration responses of the rotor. In the present work, the best conditions to apply the combination resonance approach are investigated in terms of the amplitude and frequency of the so-called diagnostic force. The vibration responses and phase angles of a cracked rotor were determined by using the harmonic balance technique. The FLEX approach is used to model the crack. Numerical simulations were performed using the finite element model of a horizontal rotor.